(3GdCeGdjs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3gPg GdChQGb CHjGJ CNPJ HMVQI GHf GdMGLH, Jcde Ydi eYGfjgG hEYQGHgG ef TYQ GdYQH hGdeJfHj hZjQgG ef GdTYQGA s
(3BNQgG (B:s
(3adjS jCJjc efgjgG hdG bGUQ Yfc eCehQgG cCfg YGFO Ydi GdefgjGJ dONhdgG aj GdCehQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdCeGdj Ydi TYQ GdeJfHj hHYV GdYQH hHYV GdTYQGA hZjQges
(3hGdfSNI ebGHdI hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs